Selenium-modified hydroxyapatite titanium coating: enhancing osteogenesis and inhibiting cancer in bone invasion by head and neck squamous cell carcinoma - Wen, Xutao; Zhou, Qin; Lin, Sihan; Mai, Huaming; Zhang, Ling (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionHead and neck squamous cell carcinoma (HNSCC) frequently invades the jaw, and surgical treatment often leads to bone defects requiring reconstruction with titanium plates. To enhance the anti-tumor and bone regeneration properties of titanium, a selenium-modified hydroxyapatite coating was developed on titanium surfaces.MethodsSelenium-modified hydroxyapatite coatings was fabricated using micro-arc oxidation (MAO). The coating properties were characterized by SEM, XPS, AFM, Contacting angle test and ICP-OES. Cell proliferation assays were performed using rBMSCs and Cal27 cells. The osteogenic potential of the materials was assessed via ALP and OCN immunofluorescence staining and quantitative polymerase chain reaction (qPCR). Apoptosis in Cal27 cells was analyzed through flow cytometry, and ROS levels in rBMSCs and Cal27 cells were measured using ROS fluorescent probes.ResultsA coating was successfully formed on the surface of titanium with a porous structure via MAO. The atomic percentages of calcium, phosphorus and selenium on the coating surface were 42.47%, 45.43% and 12.3%, respectively, and the ion components could be released steadily and slowly. In vitro, 0.2 µg/mL selenium had toxic effects on Cal27 and promoted osteogenic differentiation of rBMSCs. PCR showed that selenium increased the expression of genes related to osteogenic differentiation of rBMSCs by 3–5 times. ROS detection found differences in intracellular ROS content between Cal27 and rBMSCs.DiscussionBy incorporating selenium-modified coatings, titanium implant materials can simultaneously promote osteogenesis and inhibit tumor growth, offering a promising strategy for postoperative functional recovery in HNSCC patients.